Encounter with the Divine - A Study in Tiruttoqtar Puranam - Harihar, Sobana (My University, 1988)
The Tiruttontar Puranam is a late medieval Tamil , hagiography that is venerated as the last of the Saiva; Tirumurai(s) - the sacred literature of the Tamil Saivas. It was composed around the twelfth century by Cekkilar, who was minister in the court of Kulottunka II (1133 -1150). The hagiography narrates the stories of the sixty-three nayanmar , - Saiva saints, who lived between the sixth and the eighth centuries.
This thesis examines the stories of five nayanmar who are drawn to our attention by the fact that their devotion expresses itself in unusual and violent forms. While all the stories revolve around the 'encounter' between the devotee and his Lord, these five exemplify encounters with God that seem to violate all normal human values. In the tension between human and divine ties, their bhakti in its extremity leads them towards acts of violence which raise serious moral questions for most readers.
The concept of tontu (service) is identified as the over-arching principle used by Cekkilar to provide a rationale for these stories. This thesis centers on the way he uses that concept in the five stories in order to explain the occasionally violent or antinomian nature of bhakti. Recounting the stories in Cekkilar's words, this thesis traces the way in which he handles the story, and his skillful introduction of the idea of to~tu. The later tradition had to accommodate these antinomian saints within its system. Its attempt to corne to terms with these episodes of fers an interesting perspective on the tradition itself and so this thesis examines Tirukkalirrupatiyar's thirteenth century assessment of these saints as a concluding note.
Keywords: Religion; Religion